2018
DOI: 10.3389/fonc.2018.00436
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Clinical Trial in HPV+ and HPV– Head and Neck Squamous Cell Carcinoma: Impact on Cancer Cell Apoptosis and Immune Infiltrate

Abstract: Background: Metformin, an oral anti-hyperglycemic drug which inhibits mitochondrial complex I and oxidative phosphorylation has been reported to correlate with improved outcomes in head and neck squamous cell carcinoma (HNSCC) and other cancers. This effect is postulated to occur through disruption of tumor-driven metabolic and immune dysregulation in the tumor microenvironment (TME). We report new findings on the impact of metformin on the tumor and immune elements of the TME from a clinical trial of metformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Mitochondria and energy metabolism disruption play an important role in cell death. This is a hot topic, and nowadays, several therapeutic approaches are exploiting and targeting it, as is the case of metformin, currently under clinical trials [16,17]. In this regard, TFP-treatment demonstrates a great anticancer effect because it is able to target mitochondria and induce metabolic-driven cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria and energy metabolism disruption play an important role in cell death. This is a hot topic, and nowadays, several therapeutic approaches are exploiting and targeting it, as is the case of metformin, currently under clinical trials [16,17]. In this regard, TFP-treatment demonstrates a great anticancer effect because it is able to target mitochondria and induce metabolic-driven cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study of head and neck squamous cell carcinomas (HNSCC), Metformin was shown to differentially impact HNSCC subtypes with greater apoptosis in human papilloma virus negative (HPVÀ) HNSCC compared to human papilloma virus positive (HPV+) oropharyngeal squamous cell carcinoma. Moreover, the study presented the first in vivo human evidence that Metformin also triggers increased CD8 + Teff and FoxP3 + Tregs in the tumor microenvironment, suggesting an immunomodulatory effect in HNSCC [165]. In a double-blind, randomized, placebo controlled, multicenter study design, metformin in a daily dosage of 2,000 mg in Barrett's esophagus reduced serum levels of insulin and insulin resistance but were not associated with decrease of a biomarker of insulin pathway activation, phosphorylated S6 kinase (pS6K1), or alter epithelial proliferation or apoptosis in esophageal tissues [166].…”
Section: Metformin and Clinical Trialsmentioning
confidence: 93%
“…86 An analysis of the immunomodulatory effects of metformin in a clinical trial of head and neck squamous cell carcinoma revealed its ability to increase both CD8 + effector T-cells and FoxP3 + T reg cell infiltrates in the TME. 87 A retrospective descriptive analysis carried out in the randomized phase III OAK trial for treatment of advanced or metastatic previously-treated non-small cell lung cancer revealed an encouraging improvement of overall response rate in patients receiving concomitant metformin treatment with the anti-PD -L1 antibody atezolizumab. 88 Not surprisingly, large prospective clinical trials are currently underway to study the synergistic effect of metformin in combination with immune-checkpoint inhibitors before its recommendation as routine additive to cancer immunotherapy.…”
Section: Clinical Efficacy and Ongoing Trials Of Metformin Combined Wmentioning
confidence: 99%